A case of sjogren's reticular distrophy using multimodal imaging - Turgut, Burak; Çatak, Onur; Demir, Tamer (Gazi Eye Foundation, 2016)
Sjogren's Reticular Dystrophy is a rare retina pigment epithelium (RPE) dystrophy but usually with good prognosis. A 34-year-old woman admitted with complain of metamorphopsia in her right eye for fifteen days. Visual acuities were 5/10 in the right eye and 10/10 in the left eye. Intraocular pressures were in normal range and slit-lamp examinations did not revealed any pathological sign in both eyes. Fundoscopy showed bilateral foveal pigment alterations and subretinal pigment lines like fish a lobular network of deep retinal, pigmented deposits in macula and adjacent areas to vascular arcades, In fundus autoflourescence imaging,the lesion areas were hyperautofluorescent whileas surround areas of the lesions were hypoautofluorescent. Optical coherence tomography showed a small RPE detachment and RPE irregularities in the right eye while RPE irregularities and thickening in the sections on the lesions. Sjogren's reticular dystrophy was diagnosed based on these clinical signs and multimodal imaging findings. Multimodal imaging is useful fort he diagnosis and differential diagnosis from angioid streaks due to the similar early lesions localized at macula. © 2016 Gazi Eye Foundation. All Rights Reserved.
Multimodal görüntüleme ile bir sjögren'in retiküler distrofisi olgusu
Keywords: Multimodal imaging; Pattern dystrophy; Sjogren's reticular dystrophy